The functional implication of ATF6α in castration‐resistant prostate cancer cells. Issue 2 (6th January 2023) - Zhou, Hongqing; Zhang, Tingting; Chen, Liang; Cui, Fengzhen; Xu, Chenxiang; Peng, Jiaxi; Ma, Weixiang; Huang, Jirong; Sheng, Xia; Liu, Mingsheng; Zhao, Faming
Abstract: Stress in the endoplasmic reticulum (ER) may perturb proteostasis and activates the unfolded protein response (UPR). UPR activation is frequently observed in cancer cells and is believed to fuel cancer progression. Here, we report that one of the three UPR sensors, ATF6α, was associated with prostate cancer (PCa) development, while both genetic and pharmacological inhibition of ATF6α impaired the survival of castration‐resistance PCa (CRPC) cells. Transcriptomic analyses identified the molecular pathways deregulated upon ATF6α depletion, and also discovered considerable disparity in global gene expression between ATF6α knockdown and Ceapin‐A7 treatment. In addition, combined analyses of human CRPC bulk RNA‐seq and single‐cell RNA‐seq (scRNA‐seq) public datasets confirmed that CRPC tumors with higher ATF6α activity displayed higher androgen receptor (AR) activity, proliferative and neuroendocrine (NE) like phenotypes, as well as immunosuppressive features. Lastly, we identified a 14‐gene set as ATF6α NE gene signature with encouraging prognostic power. In conclusion, our results indicate that ATF6α is correlated with PCa progression and is functionally relevant to CRPC cell survival. Both specificity and efficacy of ATF6α inhibitors require further refinement and evaluation.